2023
DOI: 10.31545/intagr/156086
|View full text |Cite
|
Sign up to set email alerts
|

DEM modeling of wood sawdust compaction and breakage strength of pellets determined in diametral compression test

Abstract: A b s t r a c t . Sawdust from six wood species typical of Eastern Europe: beech (Fagus L.), birch (Betula L.), oak (Quercus L.), pine (Pinus sylvestris L.), poplar (Populus L.) and willow (Salix L.) with a moisture content of 8% were compacted at a compressive pressure of 120 MPa in a laboratory mould with a diameter of 10 mm. Diametral compression tests were performed to determine the mechanical strength of the pellets. Discrete element method simulations were performed to reproduce the compaction process an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Figure 5 shows high oscillations of the pulling force in the potato starch. These observations corroborate results from shear tests performed for potato starch by other authors [6,[26][27][28][29]. The oscillations of forces measured in some powders are associated with the slip-stick effect.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Figure 5 shows high oscillations of the pulling force in the potato starch. These observations corroborate results from shear tests performed for potato starch by other authors [6,[26][27][28][29]. The oscillations of forces measured in some powders are associated with the slip-stick effect.…”
Section: Resultssupporting
confidence: 91%
“…Hence, the material has a greater ability to withstand higher shear loads. When the maximum strength is exceeded, dilatation in the shear zone occurs, and strength decreases [26].…”
Section: Resultsmentioning
confidence: 99%
“…The corn groats were used in this study in an unconsolidated state of 0 kPa (bulk density) and under consolidation pressures of 40 and 80 kPa, respectively, corresponding to pressures prevailing in industrial silos (0 kPa-upper free layer of bulk material; 40 kPa-approximately 3 m below the upper free layer of bulk material; and 80 kPaapproximately 6 m below the upper free layer of bulk material; approximate calculations for medium-slender and low silos) [21,22].…”
Section: Methodsmentioning
confidence: 99%
“…They occur as a consequence of compaction and dilatation around the shear region in the material [22]. Many bulk solids of plant origin exhibit this peculiar behavior, including wheat flour, maize starch, potato starch, and milk powder [23][24][25]. It was found that the slip-stick response is affected by, among other factors, shear velocity, coefficient of interparticle friction, stiffness of the material, and its compressibility [20,[26][27][28].…”
Section: Evolution Of the Pulling Force Over Timementioning
confidence: 99%